Introduction of social benefits to the tera – gas turbines and pipelines - Ojo, Oluwatayo Babatope (Cranfield University, 2023)
The aim of this work is the techno-economic and environmental risk analysis (TERA) of the Trans-Saharan Gas Pipeline on gas turbine compressor stations. A pipeline project encompasses many aspects, viz., choice of compressor station location, power of each compressor station, compressor station availability, pipeline sizing, and it includes socioeconomic impacts. Therefore, this research considered the impacts of engine availability, compressor station location, and socioeconomic impact in the TERA for pipelines while optimising for the lowest lifecycle cost. The pipeline and gas compressor modules were evaluated considering segmented pipe length, elevation, and station location ambient temperature variation at varying flow conditions. The design and off-design points performance of the selected gas turbine models were simulated using Turbomatch to obtain essential performance data required for the techno socio- economic analysis. The unit availability was evaluated based on a developed local maintenance schedule and failure rate retrieved from literature studies. The analysis considered the social impacts and benefits of compressor station locations. A scenario-based techno socio-economic analysis was performed to show the sensitivities of the compressor station and pipeline systems to social and technical aspects of the project in terms of social benefits and availabilities. The economic model was developed based on social benefit algorithms and the variation in compressor station location ambient temperatures at varying flow conditions. Results show compressor station system availabilities of 0.2542, 0.4657, and 0.9926 with corresponding lifecycle costs of $22.22 billion, $23.05 billion, and $24.11 billion assuming a 15% discount rate for scenarios 1, 2, and 3, respectively. An increase in availability leads to a corresponding increase in the lifecycle cost estimate. The employment and road benefit ratios would increase by a factor of 10 and reciprocal of new locations. This ratio is for every 10 km decrease in the distance at each station location. Results show the significance of the modelling and optimisation approaches utilised in this research for compressor station locations optimisation of the integrated pipeline TERA. This will guide decision-makers on the ultimate selection of engine configurations that will give the optimum lifecycle cost and socio-economic benefits at the optimised station locations.
Igie, Uyioghosa - Associate Supervisor
Keywords: Compressor Station; Location Optimisation; Availability; Social Impact; Techno socio-economic; Ambient Condition; Lifecycle Cost; Gas Compressor; Employment Benefit; Road Benefit; Algorithm